Informing students about college: An efficient way to decrease the socio-economic gap in enrollment: Evidence from a randomized field experiment - Frauke Peter; Christa Katharina Spieß; Vaishali Zambre (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Although the proportion of students enrolled in college increased in the last decades, students from non-college family backgrounds remain underrepresented in higher education around the world. This study sheds light on whether the provision of information in a randomized controlled trial with more than 1,000 German high school students results in higher college enrollment rates. One year prior to high school graduation, we treated students in randomly selected schools by giving an in-class presentation on the benefits and costs of higher education as well as on possible funding options for college education. We collected data from students prior to the information intervention and followed them for four consecutive years. We find evidence that an information intervention increases students' application as well as their enrollment rates, in particular for students from non-college backgrounds with enrollment intentions prior to treatment. Moreover, treated students persist in college at a similar rate as students in the control group, i.e. they are not more likely to drop out of college. Our results indicate that a low-cost information intervention is an efficient tool to encourage students to translate their college intentions into actual enrollment.
Keywords: I21; I24; J24; 330; college enrollment; college benefits; college costs; educational inequality; information; randomized controlled trial